2021
DOI: 10.1155/2021/9327363
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitudes, and Management of General Practitioners of the Hospital Districts of Ouagadougou about Migraine (Burkina Faso)

Abstract: Background. Migraine is a common neurological disorder characterized by severe headache attacks that may be debilitating. The objective of this study is to determine the knowledge and attitudes of general practitioners in the hospital districts of the city of Ouagadougou on migraine. Methods. This cross-sectional study was carried out in hospital districts of Ouagadougou. The data were collected during three months from February 1 to April 30, 2020. Results. The study included 116 general practitioners. Thirte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 25 publications
(29 reference statements)
0
1
0
Order By: Relevance
“…This minimal difference may be attributed to misdiagnosis by healthcare providers or misperception by patients because patients were asked about the diagnosis they received from the HCP in this study [35]. This possibly highlights the inadequate professional health information concerning headaches and their different diagnoses, the lack of use of the International Classification of Headache Disorders-3, which was noticed in a few previous studies, plus, the lack of knowledge regarding preventive measures that can reduce headache attacks [7,23,26]. There is a need for greater professional education and health awareness to overcome the misdiagnosis of headaches and provide satisfying healthcare to patients who suffer from headaches [6,27].…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…This minimal difference may be attributed to misdiagnosis by healthcare providers or misperception by patients because patients were asked about the diagnosis they received from the HCP in this study [35]. This possibly highlights the inadequate professional health information concerning headaches and their different diagnoses, the lack of use of the International Classification of Headache Disorders-3, which was noticed in a few previous studies, plus, the lack of knowledge regarding preventive measures that can reduce headache attacks [7,23,26]. There is a need for greater professional education and health awareness to overcome the misdiagnosis of headaches and provide satisfying healthcare to patients who suffer from headaches [6,27].…”
Section: Discussionmentioning
confidence: 84%
“…Most primary headache disorders can be managed in the community setting through medications that are easily accessible. However, general practitioners need knowledge and experience on when and how to prescribe abortive and preventive medication [7,23]. Furthermore, a general practitioner can diagnose and manage most of the headache disorders by following guidelines from the ICHD and other headache institutes [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…The sample group participating in the study were monitored over the course of four migraine attacks: two before and two during application period. It was discovered that placing a cold band around the forehead reduced pain intensity while also enhancing quality of life 11 , The study showed that Out of 52 participants having headache only 5 participants 9.6% reported that they visited hospital because of headache that In contrast to preventive treatment, a study in 2021 indicated that the majority of general practitioners were familiar with the diagnostic criteria and acute management of migraine 23 .…”
Section: Discussionmentioning
confidence: 99%